(untitled) (Archaeologia Adriatica, 2025)
The prehistoric hillfort settlement of Grad in Nakovana is one of the most prominent Bronze and Iron Age settlements on the southern part of the eastern Adriatic coast. Its importance and the complex wider cultural landscape are reflected not only in the material legacy found so far, but also in the numerous stone mounds around Grad, especially on the hill of Zmijna. Since it was presumed that Grad was continuously inhabited until the end of the Iron Age, it was expected to find flat graves, which were in fact discovered during the excavations of 2020. On the southern slopes of Zmijna hill, two flat graves were discovered near younger stone mounds. The grave located near the top of the hill was dated to the Early Iron Age based on the finds. The remains of several individuals were laid in a natural depression and covered with large stone blocks. The grave contained potsherds, but also jewellery and costume items indicating cultural contacts with the hinterland and the area of the western Balkans, where the Early Iron Age was characterized by the development of the Glasinac culture.